2003
DOI: 10.1029/2002ja009579
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence distributions of the auroral kilometric radiation ordinary and extraordinary wave modes

Abstract: [1] Occurrence distributions of the auroral kilometric radiation (AKR) and its right-hand extraordinary (R-X ) and left-hand ordinary (L-O) wave modes are determined from polarization measurements on Interball-2 (Auroral). The AKR is much less frequent on the dayside (20% of the observing time) than on the nightside (70%). A bulk of its occurrence extends from invariant latitude of 80 at afternoon hours of MLT to 60 at night hours. Like the nightside AKR, the dayside one is generated through the electron-cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Internal Z mode is also detected in the source region [ Gurnett et al , 1983], but may result from conversion of RX mode radiation propagating normal to the auroral cavity [ Pritchett et al , 2002]. Although the RX mode almost always dominates observed AKR emission, there is often significant power in the LO mode, usually in the range 1%–10% of the RX power [ Mellott et al , 1984; Benson et al , 1988; Hanasz et al , 2003]. When LO and RX mode are seen together, their observed fluxes are often highly correlated, with LO mode flux densities about 2% of RX mode [ Mellott et al , 1984].…”
Section: Introductionmentioning
confidence: 99%
“…Internal Z mode is also detected in the source region [ Gurnett et al , 1983], but may result from conversion of RX mode radiation propagating normal to the auroral cavity [ Pritchett et al , 2002]. Although the RX mode almost always dominates observed AKR emission, there is often significant power in the LO mode, usually in the range 1%–10% of the RX power [ Mellott et al , 1984; Benson et al , 1988; Hanasz et al , 2003]. When LO and RX mode are seen together, their observed fluxes are often highly correlated, with LO mode flux densities about 2% of RX mode [ Mellott et al , 1984].…”
Section: Introductionmentioning
confidence: 99%
“…Satellites that investigated these auroral regions have observed that the radiation is emitted in the extraordinary (X) plasma mode , Ergun et al 2000, polarized and propagating perpendicular to the static magnetic field. More distant observations indicate some small fraction is also polarized in the ordinary (O) mode (Hanasz et al 2003). In the magnetosphere a parallel electric field, E , is necessary to constantly accelerate the electrons into the converging magnetic field to obtain the AKR distribution (Wu andLee 1979, Pritchett andWinglee 1989) and reduce the plasma density.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the occurrence distribution of L-O mode is less than that of R-mode [30] and L-X mode lies in a very limited frequency range. Since the diffusion coefficients depend on the wave occurrence distribution and the resonant frequency also depends on the wave frequency range, the acceleration produced by L-O and L-X modes should be less efficient than by R-X mode.…”
Section: Resultsmentioning
confidence: 92%